Assessment of Bacterial Leaf Blight Disease of Indonesian Rice Germplasms Using SSR Markers - Fatimah, Fatimah; Tasliah, Tasliah; Prasetiyono, Joko; Mahrup, Mahrup (Annales Bogorienses, 2020)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is a serious disease in rice plants worldwide. Yield losses caused by Xoo can be as high as 50% in some parts of Asia. Xa7 gene can potentially confer a broad resistance to BLB. Evaluation of disease resistance characteristics in early breeding generations of rice is important to develop varieties with better resistance. This study reports the evaluation of 167 Indonesian rice germplasms against three BLB isolates/pathotypes in a green house setting and the genotyping of 56 Indonesian rice germplasm using 12 SSR markers linked to Xa7 BLB resistance gene. The majority of the indigenous rice germplasms was found to be susceptible to three BLB isolates/pathotypes tested. Sate Liko from Bantul, Yogyakarta, Horeg from Cirebon, West Java and Sijem from Malang, East Java revealed consistent resistance to three isolates/pathotypes tested based on BLB evaluation in a greenhouse, UPGMA analysis, and genotyping. Pathotype XII displayed more virulence to Indonesian rice varieties tested compared to pathotypes VI and V. The association analysis using the General linear model identified six markers associated with BLB resistance and two markers were highly associated (RM20589 and RM20590). This information will be useful for future studies of BLB resistance in rice plants.